ANALISIS PENGGUNAAN E-RESOURCES OLEH MAHASISWA FEBI UIN SALATIGA: PENDEKATAN TECHNOLOGY ACCEPTANCE MODEL - M. Muqtafin (Pustabiblia: Journal of Library and Information Science, 2025)
This study aims to determine what factors influence the use of UIN Salatiga library e-resources using the TAM (Technology Acceptance Model) model. The sample used in this research is active students of the Faculty of Economics and Islamic Business (FEBI) UIN Salatiga. The method used in this research is the Structural Equation Model-Partial Least Square (SEM-PLS). The results showed that all variables in the TAM model can significantly explain the use of UIN Salatiga library e-resources. However, information literacy does not have a significant effect on the perceived usefulness and usage of UIN Salatiga library e-resources. The results of this study provide useful information, especially for the management of UIN Salatiga Library to continue to socialize regularly with students regarding the services owned by the library, including e-resources, in order to encourage students to be able to use these services to obtain quality reference sources.